Haptic Cues Used for Outdoor Wayfinding by Individuals with Visual Impairments. (January 2014) - Koutsoklenis, Athanasios; Papadopoulos, Konstantinos
Introduction: The study presented here examines which haptic cues individuals with visual impairments use more frequently and determines which of these cues are deemed by these individuals to be the most important for way-finding in urban environments. It also investigates the ways in which these haptic cues are used by individuals with visual impairments. Methods: To answer the research questions, both quantitative and qualitative data were collected. The data collection procedure consisted of three parts: a focus-group interview, questionnaires, and fully structured interviews. Results: A list of 37 haptic cues used for outdoor wayfinding emerged from the focus-group interview. The following haptic cues were calculated to be the most significant for outdoor wayfinding by individuals with visual impairments: changes in the texture of walking surface, sidewalks, bus stops, slopes, curb ramps, walls, parking posts, traffic lights, flower beds, and potholes. Participants use these haptic cues as points of reference, to determine their position in an environment, and to collect information about other objects in the environment. Haptic cues also function as warnings of possible hazards and help individuals with visual impairments to avoid colliding with objects while walking. Discussion: The participants reported that they use haptic cues that can be perceived through different means and that they use their sense of touch to gain different types of spatial information. A discrepancy was revealed for several cues between their scores in frequency and usefulness. Implications for practitioners: Findings from this study could be used to inform training in orientation and mobility, to enhance route descriptions, and to inform the design of commercial tactile maps.